Drosophila D-titin is required for myoblast fusion and skeletal muscle striation. - Zhang, Y.; Featherstone, D.; Davis, W.; Rushton, E.; Broadie, K. (Journal of Cell Science, 2000)
An ethylmethane sulfonate (EMS) mutagenesis of Drosophila melanogaster aimed at discovering novel genes essential for neuromuscular development identified six embryonic lethal alleles of one genetic locus on the third chromosome at 62C. Two additional lethal P element insertion lines, l(3)S02001 and l(3)j1D7, failed to complement each other and each of the six EMS alleles. Analysis of genomic sequence bracketing the two insertion sites predicted a protein of 16,215 amino acid residues, encoded by a 70 kb genomic region. This sequence includes the recently characterized kettin, and includes all known partial D-Titin sequences. We call the genetic locus, which encodes both D-Titin and kettin, D-Titin. D-Titin has 53 repeats of the immunoglobulin C2 domain, 6 repeats of the fibronectin type III domain and two large PEVK domains. Kettin appears to be the NH2-terminal one third of D-Titin, presumably expressed via alternative splicing. Phenotype assays on the allelic series of D-Titin mutants demonstrated that D-Titin plays an essential role in muscle development. First, D-Titin has an unsuspected function in myoblast fusion during myogenesis and, second, D-Titin later serves to organize myofilaments into the highly ordered arrays underlying skeletal muscle striation. We propose that D-Titin is instrumental in the development of the two defining features of striated muscle: the formation of multi-nucleate syncitia and the organization of actin-myosin filaments into striated arrays.